A balanced approach to identifying, prioritising and evaluating all potential consequences of quality improvement: modified Delphi study. Issue 3 (23rd March 2019) - Toma, Madalina; Dreischulte, Tobias; Gray, Nicola M; Guthrie, Bruce
Abstract : Objectives: Healthcare is a complex system, so quality improvement will commonly lead to unintended consequences which are rarely evaluated. In previous qualitative work, we proposed a framework for considering the range of these potential consequences, in terms of their desirability and the extent to which they were predictable or expected during planning. This paper elaborates on the previous findings, using consensus methods to examine what consequences should be identified, why and how to prioritise, evaluate and interpret all identified consequences, and what stakeholders should be involved throughout this process. Design: Two-round modified Delphi consensus study. Setting and participants: Both rounds were completed by 60 panellists from an academic, clinical or management background and experience in designing, implementing or evaluating quality improvement programmes. Results: Panellists agreed that trade-offs (expected undesirable consequences) and unpleasant surprises (unexpected undesirable consequences) should be actively considered. Measurement of harmful consequences for patients, and those with high workload or financial impact was prioritised, and their evaluation could also involve the use of qualitative methods. Clinical teams were agreed as important to involve at all stages, from identifying potential consequences, prioritising which of those to systematically evaluate, undertaking appropriate evaluation and interpreting the findings. Patients were necessary in identifying consequences, managers in identifying and prioritising, and improvement advisors in interpreting the data. Conclusion: There was consensus that a balanced approach to considering all the consequences of improvement can be achieved by carefully considering predictable trade-offs from the outset and deliberately pausing after implementation to identify any unexpected surprises and make an informed decision as to whether quantitative or qualitative evaluation is needed and feasible. Stakeholders' roles in in the process of identifying, prioritising, evaluating and interpreting potential consequences should be explicitly addressed within planning and revisited during and after implementation.